Factors related to good food-handling practices: a cross-sectional study based on male food handlers in catering establishments - Yujuan Chen; Jiangen Song; Jiajia Dai; Wei Shi (BMC Public Health)
Abstract Background Male food handlers in catering service establishments play an important role in food safety issues in China. However, their food-handling practices are not fully understood. This study aimed to assess the level of food-handling practices and identify factors associated with good practices among male food handlers in these establishments. Methods A cross-sectional survey was conducted among 648 male food handlers at randomly selected catering service locations in Wuhu City, Anhui Province, China. A self-compiled questionnaire was used to gather data on the food handlers' demographic characteristics and food-handling practices. Results The majority of interviewees (648) had good food-handling practices such as washing hands with soap before handling food (91.2%), checking for any deterioration of food (92.6%), infrequently using food additives beyond their scope and usage limits (92.9%), and infrequently using recycled food as a raw material for new food production (93.8%). However, compliance rates for certain food-handling practices remain low. These include using a 3-compartment sink to wash animal-based, plant-based, and seafood-based foods separately (28.1%), storing perishable cooked foods at appropriate temperatures (38.3%), and using dedicated containers or tools for storing and processing different food materials (42.1%). Age 50 years and above was negatively correlated with good practices when compared to those aged 18 to 30. Average monthly incomes ranging from 3,000 to 4,999 (CNY) and 5,000 to 6,999 (CNY), work experience of 3 to 4 years and 9 years or more, as well as having received food safety training, were positively correlated with good practices, in contrast to incomes below 3,000 (CNY), work experience of less than 1 year, and the absence of food safety training, respectively. Conclusions Strengthen food safety training for male food handlers in catering service establishments, particularly targeting older and inexperienced ones, to enhance their food handling skills.